Investigation of diclofenac degradation in a continuous photo-catalytic membrane reactor. Influence of operating parameters - Sarasidis, Vasilis C.; Plakas, Konstantinos V.; Patsios, Sotiris I.; Karabelas, Anastasios J. (Chemical engineering journal (Lausanne, Switzerland : 1996), 2014)
•Successful application of submerged-type PMR system for diclofenac degradation.•Steady state operation with more than 96% diclofenac degradation.•Highest TOC removal with near optimum operating parameters pH∼6, TiO2 0.5g/L.•Significant effect of feed water composition on diclofenac mineralization.•Negligible membrane fouling in long-term continuous operation of the PMR system. A laboratory pilot photocatalytic membrane reactor (PMR), employing a hybrid TiO2/UV-A catalysis–ultrafiltration process, is evaluated for degradation of diclofenac (DCF), a typical micro-pollutant frequently encountered in source waters. The combination of membrane ultrafiltration with photocatalysis allows TiO2 separation and reuse whereas the automatic periodic membrane backwashing, combined with moderate permeate flux, effectively control membrane fouling, thus permitting stable continuous operation with no wastewater stream. The operation under steady state conditions permitted the assessment of the PMR system performance (for DCF degradation), in terms of water pH and catalyst dosage, in relatively long-term tests. The results demonstrate excellent system performance. Experiments with groundwater, at UV-A radiant power per unit volume 6.57W/L, show an optimum DCF removal at pH∼6 and TiO2 loading near 0.5g/L with maxima of DCF molecular degradation and mineralization ∼99.5% and ∼69%, respectively. Significant differences of photo-catalytic oxidation performance are identified with different water matrices (i.e. ultrapure water, tap water, groundwater), confirming the important role of feed-water characteristics (i.e. presence of organic and inorganic scavengers) on process effectiveness. The new results highlight, among other factors, the need for good knowledge of feed water properties, to successfully design a PMR treatment process for effectively removing organic micro-pollutant.